Kontribusi Mahasiswi KKN dalam Mengajar Dirosa di Desa Toddopulia Kecamatan Tanralili Kabupaten Maros - Syamsiah Nur; Nurfiah, Nurfiah (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze the contribution of KKN students in teaching DIROSA (Quranic Education for adults) in Toddopulia Village, Tanralili District, Maros Regency. The program aims to improve the ability to read the Quran, provide a basic understanding of Islamic science, and improve the quality of religious education in the village. Implementation methods include socialization with village officials, survey and data collection of participants, formation of learning groups based on ability, agreeing on a schedule that suits participants' busy schedules, implementation of teaching with interesting modules, periodic evaluation to measure participants' progress, and documentation and activity reports. Results showed significant improvement in participants' Quran reading skills and religious understanding, as well as strengthening social ties between female students and the local community. This research makes a real contribution in developing an effective Al-Quran teaching model, which can be applied in other villages with similar conditions.